Efficient Extraction of Past Seawater Pb and Nd Isotope Signatures From Southern Ocean Sediments. (16th March 2021) - Huang, H.; Gutjahr, M.; Kuhn, G.; Hathorne, Ed C.; Eisenhauer, A.
Abstract: Radiogenic lead (Pb) and neodymium (Nd) isotope compositions extracted from authigenic phases in marine sediments are sensitive tracers to reconstruct past ocean circulation and water mass mixing. Chemical reductive leaching of hydrogenetic ferromanganese oxyhydroxides from bulk sediments is the most practical way to recover past seawater Pb and Nd isotope signatures in the Southern Ocean, due to the scarcity of alternative archives. However, the leached signal could be compromised if substantial quantities of Pb and Nd were released from non‐hydrogenetic sediment fractions during chemical extraction. Here we developed a very short 10‐s leaching method to extract reliable seawater Pb and Nd isotope signals from sediments in the Atlantic sector of Southern Ocean. The effect of a previously recommended MgCl2 pre‐wash, the role of chelate ligands in the leaching solution and length of leaching time were investigated. The results show that 10‐s exposure time of sediments to reductive leaching extracted sufficient and more reliable hydrogenetic Pb and Nd compared with the commonly used 30‐min leaching approaches. The robustness of our improved leaching method was validated via direct comparison of Pb and Nd isotope signatures with actual seawater, porewater, and corresponding sediment leachates from three stations in front of the Antarctic Filchner‐Rønne Ice Shelf. Our findings also indicate that in contrast previously studied sites on the West Antarctic continental shelf, the bottom seawater Nd concentration is less elevated through benthic fluxes in the area of the southern Weddell Sea shelf. Plain Language Summary: Individual modern ocean water masses can often be identified by the isotopic signature of dissolved trace metals lead (Pb) and neodymium (Nd) supplied from surrounding continents. By analyzing past seawater Pb and Nd isotope ratios preserved in the sedimentary archives, we can understand how the ocean circulation changed. In the Southern Ocean, archives preserving past seawater Pb and Nd isotope compositions are very scarce. Thus, the chemical extraction of Pb and Nd from seawater‐derived ferromanganese oxyhydroxides within deep marine sediments becomes the most practical way to recover past seawater signal. However, Southern Ocean sediments commonly contain substantial quantities of Antarctic continental fine‐grained sediment, which easily partially dissolve during extraction, thereby releasing Pb and Nd, which did not originate from past ambient seawater. Here we established a gentle and efficient extraction method to obtain reliable past Southern Ocean seawater signatures. In addition, via analysis of regional seawater‐derived Pb and Nd signatures in the Atlantic sector of Southern Ocean, we found that the sediments further away from Antarctica and volcanically active regions are better suited to preserve unaltered seawater Pb and Nd isotope signals, which strongly supports the unique possibility of tracing past water mass sourcing in the Southern Ocean with our analytical approach. Key Points: 10‐s reductive leaching is capable of reliably extracting seawater Pb and Nd isotope signals from Southern Ocean sediments Natural porewater Pb isotopic compositions are analyzed for the first time in front of the Antarctic Filchner‐Rønne Ice Shelf Identify potential sites for extracting seawater Pb and Nd isotopic signatures from bulk sediments in the Atlantic sector of Southern Ocean